Magnetic signatures and origins of ferromagnetic minerals in Chang’e-6 lunar farside soils - Jinhua Li; Lin Xing; Zheng Gong; Jiawei Liu; Yan Liu; Weiwei Wu; Kelei Zhu; Yuqin Wang; Xu Tang; Lixin Gu; Yi Chen; Qiuli Li; et al. (Nature Communications)
Abstract Ferromagnetic minerals in lunar materials record key information regarding the Moon’s ancient dynamo, impact events, and space weathering. However, interpreting the magnetic signals is complicated by their diverse origins and properties. Here, we present comprehensive magnetic and mineralogical results of farside lunar soils returned by Chang’e-6 mission from the South Pole-Aitken Basin. Compared to nearside samples, these soils exhibit higher magnetic susceptibility and saturation magnetization, and the highest saturation remanence, despite weak local crustal magnetic anomalies. Advanced electron microscopy reveals two primary mineralogical populations: nickel-poor iron particles with euhedral shapes in basalt clasts (magmatic origin) and nickel-rich metallic iron and Fe-Ni alloys in breccias, agglutinates, and glassy materials (impact origin). These findings offer insights into the formation of magnetic minerals on the lunar farside, thereby enhancing our understanding of lunar dynamo evolution and crustal magnetic anomalies.